A CIPP Evaluation of Project- Based Learning Implementation in Fashion Design Programs at Vocational High Schools in Majene Regency, Indonesia - Hamriyani Hamriyani; Hamidah Suryani; Anas Arfandi (Sakura Digital Nusantara, 2026)
Purpose: This study evaluated the implementation of Project-Based Learning (PjBL) in Fashion Design Programs at vocational high schools in Majene Regency, Indonesia, using the Context, Input, Process, and Product (CIPP) evaluation model. The study addressed the limited availability of comprehensive evaluations of PjBL implementation in vocational education, particularly those examining contextual conditions, resource readiness, implementation processes, and learning outcomes simultaneously. Methods: This program evaluation employed a descriptive quantitative approach at three vocational high schools offering Fashion Design Programs in Majene Regency. The participants comprised 126 respondents, including three principals, three vice principals for curriculum, 21 vocational teachers, and 99 students selected through purposive sampling. Data were collected using four-point Likert-scale questionnaires supported by observations, semi-structured interviews, and documentation. The questionnaire was developed based on the CIPP framework and validated through expert judgment to ensure content relevance and clarity. Quantitative data were analyzed using descriptive statistics and percentage-based categories, while qualitative data were used to support the interpretation of the findings through triangulation. Findings: The evaluation indicated that the implementation of PjBL was categorized as Very Good across all CIPP components. The Context component obtained the highest evaluation result (98.3%), followed by Process (90.1%), Input (88.4%), and Product (82.5%). The findings showed that PjBL implementation was supported by curriculum alignment, school policies, and institutional commitment. However, practical facilities, industry collaboration, and the quality of student products were identified as aspects requiring further improvement. Research Implications: The findings demonstrate the applicability of the CIPP model as a comprehensive framework for evaluating PjBL implementation in vocational education. The results also provide evidence-based recommendations for strengthening school–industry partnerships, improving practice facilities, and refining project implementation to support continuous quality improvement in vocational education. Originality: This study provides a comprehensive CIPP-based evaluation of PjBL implementation in Fashion Design Programs across three vocational high schools in Majene Regency, offering empirical evidence to support program evaluation and decision-making in vocational education